Impact of sickle cell disease on presentation and progression of paediatric HIV: a retrospective cohort study. Issue 7 (11th May 2020) - Ssenyondwa, Joseph; George, Paul E.; Carlos Bazo‐Alvarez, Juan; Mercedes, Rebecca; Kanywa, Jacqueline B.; Naturinda, Ernest; Wasswa, Peter L. M.; Lubega, Joseph
Abstract: Objectives: HIV and sickle cell disease (SCD) are significant causes of morbidity and mortality in sub‐Saharan Africa. Given their separate roles in immune dysregulation, our objective was to characterise the impact that SCD has on the presentation and progression of paediatric HIV. Methods: The study was a retrospective cohort study (study period 2004–2018). Cases of HIV + and SCD‐afflicted patients (HIV+/SCD+) were obtained via electronic chart review from a paediatric HIV clinic in Kampala, Uganda and matched 1:3 with HIV + controls without SCD (HIV+/SCD‐). Results: Thirty‐five HIV+/SCD + subjects and 95 HIV+/SCD‐ controls were analysed (39% female (51/130), age 3.6 years (SD3.9)). At baseline, WHO clinical stage (64% total cohort Stage III/IV) and nutritional status (9.4% severe acute malnutrition) were similar for both groups, whereas HIV+/SCD + had higher though non‐significant baseline CD4 count (1036 (SD713) vs 849 (SD638) cells/microlitre, P  = 0.20, two‐tailed t‐test). There were 19 deaths, 6 (17%) HIV+/SCD + and 13 (14%) HIV+/SCD‐, with unadjusted/adjusted models showing no significant difference. Nutritional progression and clinical stage progression showed no significant differences between groups. Kaplan–Meier analysis showed a slower rate of treatment failures in the HIV+/SCD + cohort ( P  = 0.11, log‐rank survival test). Trajectory analysis showed that in the time period analysed, the HIV+/SCD + cohort showed a more rapid rise and higher total CD4 count ( P  = 0.012, regression analysis). Conclusion: The study suggests that SCD does not adversely affect the progression of HIV in patients on ART. Further, HIV+/SCD + achieved higher CD4 counts and fewer HIV treatment failures, suggesting physiological effects due to SCD might mitigate HIV progression. Abstract : Objectifs: Le VIH et la drépanocytose (SCD) sont des causes importantes de morbidité et de mortalité en Afrique subsaharienne. Compte tenu de leurs rôles distincts dans la dérégulation immunitaire, notre objectif était de caractériser l'impact du SCD sur la présentation et la progression du VIH pédiatrique. Méthodes: Etude de cohorte rétrospective (période d'étude 2004‐2018). Les cas de patients VIH+ atteints de SCD (VIH+/SCD+) ont été obtenus par analyse des dossiers électroniques dans une clinique pédiatrique du VIH à Kampala, en Ouganda et appariés dans une proportion 1:3 avec des témoins VIH+ sans SCD (VIH+/SCD‐). Résultats: 35 sujets VIH+/SCD+ et 95 témoins VIH+/SCD‐ ont été analysés (39% de femmes (51/130), 3, 6 ans d'âge (SD3, 9)). Au départ, le stade clinique de l'OMS (64% de la cohorte totale au stade III/IV) et l'état nutritionnel (9, 4% de malnutrition aiguë sévère) étaient similaires pour les deux groupes, tandis que les VIH+/SCD+ avaient un nombre de CD4 de base plus élevé mais non significatif (1036 (DS, 713) vs 849 (DS, 638) cellules/microlitre, p = 0, 20, test t bilatéral). Il y a eu 19 décès, 6 (17%) VIH+/SCD+ et 13 (14%) VIH+/SCD‐, avec des modèles non ajustés/ajustés ne montrant aucune différence significative. La progression nutritionnelle et la progression du stade clinique n'ont montré aucune différence significative entre les groupes. L'analyse de Kaplan‐Meier a montré un taux d'échecs de traitement plus lent dans la cohorte VIH+/SCD+ ( p = 0, 11, test de survie log‐rank). L'analyse de la trajectoire a montré que dans la période analysée, la cohorte VIH+/SCD+ a montré une augmentation plus rapide et un nombre total de CD4 plus élevé ( p = 0, 012, analyse de régression). Conclusion: L'étude suggère que SCD n'affecte pas négativement la progression du VIH chez les patients sous ART. De plus, les patients VIH+/SCD+ ont atteint un nombre plus élevé de CD4 et moins d'échecs de traitement du VIH, ce qui suggère que les effets physiologiques dus à la SCD pourraient atténuer la progression du VIH.